(untitled) (International Current Pharmaceutical Journal, 2016)
Prescribing pattern is the trending topic now days to promote rational use of drug and to make the drug therapy effective. Many factors like lack of knowledge, improper guidelines and personal interest affects the prescribing behaviour of a physician. To access the prescribing pattern and its relevant features which modulates it in the sector of Lahore, A survey was conducted in which physicians of different expertise were engaged from top hospitals of public and private sector. A questionnaire was designed and 100 physicians were interviewed as per structured questionnaire. The collected data was analysed by using analytical software SPSS 22. Pharmacological factors, cost effectiveness, efficacy of drug, recommended guidelines, psychological expectations and patient adherence are some factors which a prescriber keeps in his mind while prescribing a drug. Personal benefits and polypharmacy is strongly prohibited by physicians. physicians of Lahore prefer patient benefits upon their own in prescribing a drug but there are still some drawbacks like socio-economic factor and social culture which cause hindrance for a physician while prescribing. Saleem et al., International Current Pharmaceutical Journal, November 2016, 5(12): 118-119 http://www.icpjonline.com/documents/Vol5Issue12/04.pdf